A paired trial comparing mononuclear cell collection in two machines for further inactivation through an inline or offline extracorporeal photopheresis procedure. Issue 1 (4th October 2018) - Bueno, José‐Luis; Alonso, Rosalía; Gonzalez‐Santillana, Clara; Naya, Daniel; Romera, Irene; Alarcón, Ana; Aguilar, Myriam; Bautista, Guiomar; Duarte, Rafael; Ussetti, Piedad; Cabrera, José Rafael
Abstract : BACKGROUND: Extracorporeal photopheresis (ECP) is an effective treatment. However, protocols differ widely, and some questions, such as the number of cells to be collected or the number of ECP treatment days per treatment cycle, are still unsolved. The aim of this study was to compare a multistep (offline) (Spectra Optia and Macogenic G2) against an integrated (inline) ECP system (Therakos Cellex system) with respect to mononuclear cell (MNC) collection. STUDY DESIGN AND METHODS: The number and quality parameters of the MNC products collected were evaluated together with some machine parameters, such as collection time. Comparisons were made through paired sample analysis with the t test. RESULTS: Fourteen patients underwent 15 double‐paired procedures using both ECP protocols. The average MNC collected in the multistep procedure was 77.4 × 10 8, four times more than in the integrated procedure (18.5 × 10 8 ). MNC purity (84.4% vs. 63.8%) and enrichment (27.9 vs. 5.9) in the product collected were also higher in the multistep procedure. The whole ECP time was higher in the multistep than in the integrated procedure (272 vs. 106 min), but the calculated time to collect 25 × 10 8 MNCs in the multistep was shorter compared with the one‐step procedure (77.8 vs. 172 min). All these differences between the two protocols were statistically significant. CONCLUSIONS: These two ECP protocols are different with respect to MNC collection and length of procedure. Some unresolved questions, such as the better MNC dose to inactivate or the number of consecutive days that ECP should be performed for optimal clinical efficacy, require further review.